Temporal Analysis of Viewer Engagement in One Piece: Trends in IMDb Ratings Across Arcs and Time - Poovarasan Selvaraj; Qingxue Yang (Bright Publisher, 2025)
This study examines the long-term viewer reception of One Piece, a globally influential anime series, by analyzing 1,122 episodes released between 1999 and 2023 using IMDb data. The research aims to understand how audience engagement and critical reception evolve, and how content structure, specifically narrative arcs and episode types, affects these dynamics. Quantitative analysis was conducted on episode ratings, vote counts, narrative arc segmentation, and episode classification (Canon, Filler, Semi-Filler). The findings reveal a clear upward trend in average episode ratings, increasing from 7.9 in 1999 to over 8.4 in recent years. Viewer participation also grew significantly, with total annual votes rising from 63,939 in 1999 to over 300,000 votes per year after 2020. Canon episodes achieved the highest average rating (8.22) across 996 episodes and garnered a total of 2,630,987 votes. In contrast, Filler episodes averaged 6.62 (90 episodes), while Semi-Filler episodes scored 7.14 (36 episodes). The highest-rated narrative arcs, each comprising at least five episodes, consistently achieved an average rating of 8.7 or higher and demonstrated alignment with major plot developments and emotional climaxes. These results highlight the importance of narrative relevance and continuity in maintaining audience satisfaction and fostering long-term engagement. The increasing vote volume reflects the expansion of One Piece’s global audience and the role of digital platforms in amplifying participatory behavior. This study highlights how serialized media can maintain cultural impact through strategic narrative design and evolving viewer engagement.